THE ROLE OF HALAL PRODUCT PROCESS FACILITATORS IN EXPANDING ACCESS TO HALAL CERTIFICATION SERVICES FOR MSMES IN BANDUNG CITY - Yeti Rohayati; Tati Sarihati; Shinta Dzauharoh (Al-Mubin, 2025)
Access to halal certification services for MSMEs in Bandung City remains constrained by limited procedural understanding, inadequate document readiness, low digital literacy, and weak process continuity, despite the availability of regulatory frameworks, service schemes, and the SIHALAL digital platform. This study aims to analyze the role of Halal Product Process Facilitators in expanding MSMEs’ access to halal certification services in Bandung City. The study is grounded in empowerment theory, service access theory, and service quality theory. A qualitative approach with a case study design was employed, supported by document analysis and secondary data drawn from Bandung Open Data, official publications of BPJPH and the Ministry of Religious Affairs, halal certification regulations, and SIHALAL service documents. The findings show that facilitators function as information providers, administrative assistants, technical guides, digital service intermediaries, and process enablers throughout certification completion. These results indicate that the effectiveness of halal certification depends largely on the quality of facilitation in translating regulatory and digital requirements into accessible and manageable service processes for MSMEs